Improving Graphic Design Competence Through an Internship at a Community Learning Center - Noviyanti, Ida Nur’aini; Uyu Wahyudin, Uyu Wahyudin2; Saepudin, Asep; Shantini, Yanti (Journal of Nonformal Education, 2026)
Background - A significant proportion of Community Learning Center (CLC) alumni transition directly into the workforce upon graduation rather than pursuing higher academic education. This trend necessitates the acquisition of practical life skills that are highly relevant to current labor market demands.Research Urgency - Internship programs within CLCs are pivotal in bridging the gap between classroom instruction and professional requirements. Systematic evaluation of these programs, particularly in the field of graphic design, is essential to ensure that graduates' competencies meet nationally recognized standards.Research Objectives - This study aims to evaluate the development of graphic design competencies among CLC learners through an internship program implemented during the 2022-2023 academic year.Research Method - A non-experimental quantitative approach with descriptive statistical techniques was employed. The study involved a sample of 20 CLC participants. Data collection utilized assessment rubrics adapted from the Indonesian National Work Competency Standards (SKKNI) issued by the Ministry of Manpower of the Republic of Indonesia to measure the participants' competency levels.Research Findings - The findings reveal significant competency progression among the learners. Participants who initially possessed only basic design principles at the program's inception achieved novice-level proficiency by its conclusion. This underscores the effectiveness of structured internship programs in enhancing technical skills.Research Conclusion - Competency-based internship programs are effectively proven to prepare CLC learners for successful integration into the professional landscape by fulfilling established work competency standards.Research Novelty/Contribution - This research provides a practical reference for other CLCs in designing effective internship programs, specifically in the graphic design domain, by aligning non-formal curricula with SKKNI standards to enhance graduate employability.